Childhood autism associated with neurological manifestations and corpus callosum hypoplasia: literature review and clinical cases - O. A. Komissarova; O. A. Milovanova; G. G. Avakyan; S. V. Bugriy (Эпилепсия и пароксизмальные состояния, 2020)
Aim. To consolidate literature data and to demonstrate rare hereditary neurogenetic syndromes with various neuropsychiatric manifestations and a corpus callosum (CC) structurally reduced in size.Material and methods. Full text data from scholarly journals were used for the review. Mental and neurological disorders were studied in two examined patients with neurogenetic syndromes. A brain MRI showed that it was accompanied with CC hypoplasia. We conducted comprehensive analysis of anamnestic data as well as medical genetic, neurological, psychopathological, pathopsychological, laboratory, and instrumental examinations.Results. The presented observations testified to a burdened obstetric history, dysfunctional ante-, intra-, and postnatal periods. The first patient with the Wolf-Hirschhorn syndrome was diagnosed with atypical autism associated with severe mental retardation, lack of verbal means of communication, motor stereotypes, structural focal epilepsy, cerebral palsy (CP), severe systemic speech underdevelopment; the second patient with the Prader-Willi syndrome was diagnosed with organic autism associated with mild mental retardation, impaired social adaptation in combination with stereotyped actions, impaired visual-spatial coordination, and cerebral palsy. In the first case, MRI showed posterior CC hypoplasia; in the second case, MRI showed hypoplasia of the CC isthmus.Conclusion. The level of cognitive deficit was to some extent a value associated with the thickness of the posterior CC. Apparently, a higher degree of myelination of nerve fibers contributes to a higher rate of transmission of nerve impulses along nerve fibers stimulating neurons. The results can be considered preliminary; a larger study is needed.